FENOLOGI DAN KETERSEDIAAN REGENERASI POHON NYAMPLUNG (Calophyllum inophyllum L.) DI PESISIR PANTAI KABUPATEN PADANG PARIAMAN - Fatri Juni Ardisa; Reki Kardiman; Moralita Chatri; Filza Yulina Ade (Universitas Tribhuwana Tunggadewi, 2025)
Nyamplung (Calophyllum inophyllum L.) is a key coastal species with both ecologyl and economic importance. The tree, is highly recommended for coastal zone restoration, but availability of the seeds and seedlings is less known.This study aimed to investigate flowering/fruiting phenology as well as natural regeneration availability across different in coastal zone of Padang Pariaman Regency. Weekly phenological observations and regeneration stock measurement were conducted from September to December 2025i, with 34 observed trees in the sites that ranged from ;ow to high land use level. Results showed that most trees were found flowering in September, but it was declined following the increasing of fruiting event at mid to end of October and number of the fruiting trees were declined until end of December. These flowering and fruiting phenology among the landuse types showed a similar pattern with only little variation. In general 0.12 seedlings/m², while tourism areas showed the lowest 0.03 seedlings/m² in the highest disturbed. And is was negatively correlated with distance fron the mother tree(p0.05). This study a range of flowering and fruiting phenology in Padang Pariaman Coastal areas with small variation of the phenology between landuse types, as well as variation in regeneration stock of C. inophyllum across the areas.